2018
DOI: 10.46743/2160-3715/2018.3013
|View full text |Cite
|
Sign up to set email alerts
|

“If our English isn’t a language, what is it?” Indonesian EFL Student Teachers’ Challenges Speaking English

Abstract: Research on students’ skill speaking English in a non-English speaking country such as Indonesia is limited. The purpose of this phenomenological study was to document Indonesian EFL student teachers’ experiences in speaking English at one public university in Jambi, Indonesia. Data came from demographic questionnaires and semi-structured interviews obtained from eight participants. We organized our analysis and discussion around Indonesian EFL student teachers’ perspectives and the contexts in which experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 0 publications
7
56
0
Order By: Relevance
“…Based on the fundamental task of establishing moral education, foreign languages curriculum standards have updated the content of the curriculum and emphasized the thematic contexts [1]. In foreign languages teaching, teaching design based on thematic contexts can guide students to integrate the development of language ability, cultural awareness, ideological quality and learning ability, and shape students' core foreign languages subject literacy [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the fundamental task of establishing moral education, foreign languages curriculum standards have updated the content of the curriculum and emphasized the thematic contexts [1]. In foreign languages teaching, teaching design based on thematic contexts can guide students to integrate the development of language ability, cultural awareness, ideological quality and learning ability, and shape students' core foreign languages subject literacy [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The solution which is suggested by many is that to have native or native-like language instructors or peers to assist these L2 users or learners. Abrar (2018) encountered in his research that one of the learners' preferences to learn spoken English is by listening to native speakers. In this case, it could also possibly mean that language instructors -no matter if he or she a native or native-like speaker -has to play their role and has to be genuinely responsible to really impart the knowledge and skill (in terms of instilling correct grammar usage and accurate syntax skills) to these learners; not only as language instructors but also as "educator, model, and cultural ambassador that offers a more global outlook" (Brown, 2018).…”
Section: Talk As Interaction and Transaction -The Challenges Amongst The L2 Usersmentioning
confidence: 99%
“…However, L2 learners or communicators will end up revert to their mother tongue or choose to keep silent if they are unable to express all their thoughts in English due to lack of motivation from the language instructors and lack of English language competency (Smith, 2018). Again, both intrinsic and extrinsic motivations are believed to be the factor one's could speak up confidently in which their anxiety level too is decreasing (Jang & Wood, 2019;Abrar, 2018).…”
Section: Second Language Learners' Anxiety To Speaking English -The Cause and Effectmentioning
confidence: 99%
“…This trend has also popularised the teaching of English in non-English speaking countries. Due to the increased demand for instruction in English, 80% of the English teachers in the world are non-English speakers [1]. Studies have shown that the teaching of English to non-English speakers is a complex task for student teachers [2,3].…”
Section: Introductionmentioning
confidence: 99%